IMPROVING KNOWLEDGE OF NON-COMMUNICABLE DISEASE PROGRAM MANAGERS IN TUBERCULOSIS-DIABETES MELLITUS CONTROL AND CARE - Arini, Merita; Primastuti, Harumi Iring; Basha, Muzaitul Akma Binti Mustapa Kamal (Universitas Airlangga, 2024)
Introduction: Indonesia ranks second in the number of TB cases worldwide, accounting for 10% of the total TB cases. In addition, Indonesia ranks fifth in the number of DM cases worldwide. However, the integration of TB and DM disease management programs to ensure safe and quality care in health facilities is generally insufficient. Aims: This study aims to improve the knowledge of NCD program managers regarding TB-DM and their role in TB control and care. Methods: This study used a quasi-experimental design (non-randomized and non-control group) involving all healthcare workers (HCWs) managing NCD programs in Yogyakarta City. The participants were selected from 18 community health centers, 5 hospitals, the Health Office of Yogyakarta City. Prior to and following the training sessions, the knowledge of the participants was assessed. Results: According to the results of the Kruskal-Wallis test, no significant differences in TB-DM knowledge were observed among participants based on age group, length of employment, occupation, and highest level of education. However, following the training sessions, the participants showed a significant improvement in TB-DM knowledge according to the results of the Wilcoxon signed-rank test p = 0.000, with an effect size (r) of 0.57 (95% CI [0.000, 0.113]). Conclusion: Training for NCD program managers has been shown to improve their knowledge about TB-DM and their potential roles. Therefore, it is crucial to conduct continuous capacity-building programs for HCWs. These programs should be supported by policies, systems, and necessary infrastructures to ensure effective implementation of integrated care for TB and other diseases.